Species delimitation in the genus Ochraethes Chevrolat, 1860 (Coleoptera: Cerambycidae), with description of two new species - Pérez-Flores, Óscar; Toledo-Hernández, Víctor H. (European Journal of Taxonomy, 2022)
Based on morphological and molecular data we investigated the species boundaries in the genus Ochraethes Chevrolat, 1860. The species delimitation with cytochrome c oxidase subunit 1 (COI) data supports some synonymies and highlights the existence of a high phenotypic plasticity in some species. The following species are considered as new junior synonyms: O. virescens (Chevrolat, 1860) syn. nov. of O. brevicornis (Chevrolat, 1860), O. octomaculata Chemsak & Noguera 2001 syn. nov. of Ochraethes cinereolus (Bates, 1892) comb. nov., O. zebratus Bates, 1885 syn. nov. of O. obliquus (Chevrolat, 1860), Trichoxys giesberti Botero, Santos-Silva & Wappes, 2019 syn. nov. of O. sommeri (Chevrolat, 1835), O. clerinus (Bates, 1892) of O. viridiventris (Chevrolat, 1860), O. cristoforii (Chevrolat, 1860) syn. nov. and O. litura Bates, 1885 syn. nov. of O. z-littera (Chevrolat, 1860). Two new species are described from Mexico: Ochraethes confusus sp. nov., and Ochraethes nigroapicalis sp. nov.